The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.08.15.252171
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nitric oxide prevents aortic valve calcification by S-nitrosylation of USP9X to activate NOTCH signaling

Abstract: Calcific aortic valve disease (CAVD) is an increasingly prevalent condition and endothelial dysfunction is implicated in its etiology. We previously identified nitric oxide (NO) as a calcification inhibitor by its activation of NOTCH1, which is genetically linked to human CAVD. Here, we show that NO rescues calcification by a S-nitrosylation-mediated mechanism in porcine aortic valve interstitial cells (pAVICs) and single cell RNA-seq demonstrated regulation of NOTCH pathway by NO. A unbiased proteomic approac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 56 publications
(77 reference statements)
0
14
1
Order By: Relevance
“…Further studies have demonstrated that nitric oxide activates Notch signaling in VICs through regulation of S-nitrosylation of ubiquitin specific peptidase 9, X-linked (11). Valvular osteoblast-like cells have been suggested as promising targets for the development of a novel pharmacological intervention for CAVD.…”
mentioning
confidence: 99%
“…Further studies have demonstrated that nitric oxide activates Notch signaling in VICs through regulation of S-nitrosylation of ubiquitin specific peptidase 9, X-linked (11). Valvular osteoblast-like cells have been suggested as promising targets for the development of a novel pharmacological intervention for CAVD.…”
mentioning
confidence: 99%
“…Recent studies have revealed that Usp9x is a biomarker for stemness, which is required for stem cell self‐renewal through regulation of PRC2‐mediated chromatin reprogramming via the interaction, deubiquitination and stabilization of PRC2 in mouse embryonic stem (ES) cells (Macrae & Ramalho‐Santos, 2021), or maintaining telomere length by inhibiting HIF‐1α protein degradation and activating the transcription of TERT which encodes a telomerase reverse transcriptase in breast cancer stem cells (Lu et al, 2021). In the past few years, dozens of substrates for USP9X have been identified in various cells, such as SMURF1 in breast cancer cells (Xie et al, 2013), ZBTB38 in a stable HeLa cell line (Miotto et al, 2018), PTENαin HEK293T cells (Shen et al, 2019), MIB1 in porcine aortic valve interstitial cells (Majumdar et al, 2021), and KDM4C in lung cancer cells (Jie et al, 2021). In this study, we identified TGFBR2 as a novel substrate of USP9X and demonstrated that USP9X maintains TGFBR2 protein levels, and activation of the canonical TGF‐β signaling pathway in GCs.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, also in the eNOS+/− mouse a reduced availability of NO occurs, as assessed by the impairment in acetylcholine‐induced endothelium‐dependent vasodilation that we observed in this model (Vecoli et al, 2014). Notably, it appears that NO can regulate Notch‐1 signaling in AVICs by inducing S‐nitrosylation of USP9X, which results in stabilization of the E3 ubiquitin ligase MIB1 and potentiation of the ligand‐mediated Notch‐1 activation (Majumdar et al, 2021). At low NO concentrations, USP9X is not activated by S‐nitrosylation, leading to impairment of Notch‐1 ligand endocytosis and Notch‐1 signaling (Majumdar et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There are actually several lines of evidence linking Notch‐1 signaling with the eNOS‐NO pathway. Firstly, it has been shown that in aortic valve interstitial cells (AVICs), endothelial cell‐derived NO enhances the nuclear localization of NICD and regulates the expression of Notch‐ 1 target genes, thereby preventing aortic valve calcification (Bosse et al, 2013; Majumdar et al, 2021; Wang et al, 2021). Conversely, the reduced NO production, as occurs in endothelial cell dysfunction or in eNOS knockout mice, can in turn inhibit Notch‐1 signaling in AVICs and favor aortic valve calcification (Bosse et al, 2013; Garg, 2016).…”
Section: Discussionmentioning
confidence: 99%